Effect of curing pressure on the curing behavior of an epoxy system: Curing kinetics and simulation verification. (21st September 2022) - Liang, Qun; Feng, Xi-Ping; Zhang, Kun; Hui, Xue-Mei; Hou, Xiao; Ye, Jin-Rui
Abstract: Most composites require a certain amount of pressure to cure, therefore, it is crucial to comprehend the effect of pressure on the curing reaction. Nonetheless, the majority of studies on curing reaction focus on isothermal or non-isothermal DSC measurements at ambient pressure. Using a high-pressure differential calorimetry scanner (Netzsch DSC 204HP), the curing process of a bisphenol A diglycidyl ether system is studied in order to evaluate the influence of curing pressure. The results indicate a competitive relationship between the effect of heating rate and pressure on the reaction rate, with the influence of heating rate being stronger. The reaction follows the autocatalytic model, and the average activation energy E P and pre-exponential factor A P decrease as the pressure increases. The obtained kinetics are used to simulate the process of forming composite laminates. When the thickness of laminates exceeds 18 mm, the maximum difference of the temperature and curing degree between ambient pressure and 2 MPa pressure is 20.65 °C and 0.161, respectively, indicating that the simulation results of thick composites are affected by whether the curing pressure is considered in kinetics. Graphical abstract: Image 1 Highlights: The effects of pressure and temperature on reaction rate compete. Epoxy curing kinetics are obtained and verified at different pressures. Effects of kinetic models with varied pressures on simulation are obtained.